Compound Words in Five Selected Skincare Articles from Vogue Website - Darmapatni, Ni Luh Kadek Ayu; Mulyawan, I Wayan; Indriani, Ketut Santi (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2025)
A compound word is one of the processes of creating new words. Knowing compound words will make it easier for people to increase their vocabulary because vocabulary building is essential to any education. As a student's vocabulary becomes more complex, it becomes increasingly important to understand the meaning of words and how they function as part of the overall language. Compound words are one of the first steps in a lifelong journey of vocabulary building. Not only creating new words but also creating new meanings in language. There are two aims in the research process. First, identify the types of compound words, and second, analyze the meaning of compound words. The data in this study was compound words with the five selected skincare articles as the data source. To classify the type of compound words, this study used the theory proposed by Lieber (2010). And for the meaning of the compound words, used theory proposed by Palmer (1976). Observation methods with note-taking techniques were applied in this study. A descriptive qualitative method was applied to analyze the data, which uses in-depth descriptions. The analysis was presented by informal method, in which the examined data are provided verbally. This method was used to explain the type of the compound words and explain the meaning of the compound words. There are five types of compound words found in five selected articles from Vogue Website, those are attributive endocentric, subordinative endocentric, coordinative endocentric, attributive exocentric, and subordinative exocentric. The meaning of the compound words found in 5 articles of Vogue websites are transparent meaning and opaque meaning. Keywords: Compounding, Meaning, Morphology, Semantics